Feasibility of castor (Ricinus communis) under sapota-jatropha based horti-silvi system - Minalkumar B Tandel; M.K.Desai; M. J. Dobriyal; S. M. Patel (Indian Journal of Agroforestry, 2026)
The investigation on “Feasibility of Castor (Ricinus communis) under Sapota-Jatropha based Horti-Silvi system” was carried out at Agronomy Farm (Block-E), Navsari Agricultural University, Navsari, Gujarat, during Kharif 2015 and 2016. The experiment was comprised of five treatments and four replications in Randomized Block Design. The eleven years old plantation of Sapota [Manilkara achras (Mill.) Fosberg] planted at 10 x 10 m spacing along with nine year old plantation of Jatropha (Jatropha curcas L.) which was planted at 2.5 x 2.5 m spacing used for intercropping study. Castor (Ricinus communis L.) was grown as an intercrop. The pooled data of two years were presented in respective tables. Growing of Castor crop as sole crop resulted in significant increase in various growth as well as yield parameters as compared to growing under Sapota-Jatropha based horti-silvi system. The plant height (123.25 cm), number of branches per plant (8.13), fresh weight of plant (2875.63 g), dry weight of plant (948.75 g), number of spikes per plant (9.88), number of capsules per spike (80.63), yield per plant (272.00 g), yield per plot (9.00 kg), yield per hectare (2525.00 kg) and total biomass (148.47 q/ha) were registered significantly higher in T5: Castor sole crop, followed by T1: Castor with sole Sapota. Whereas, oil content of castor was found non-significant. The net realization (Rs. 68,343/ha) was found highest in T2: Castor with 100% pruned Jatropha under Sapota-Jatropha based horti-silvi system as compared to Castor sole crop. However, maximum cost benefit ratio (1:2.02) was noted in T5: Castor sole crop as compared to Sapota-Jatropha based horti-silvi system.